2021
DOI: 10.1111/ajt.16263
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between antithymocyte globulin, T cell phenotypes, and clinical outcomes in pediatric kidney transplantation

Abstract: Depletional induction using antithymocyte globulin (ATG) reduces rates of acute rejection in adult kidney transplant recipients, yet little is known about its effects in children. Using a longitudinal cohort of 103 patients in the Immune Development in Pediatric Transplant (IMPACT) study, we compared T cell phenotypes after ATG or non‐ATG induction. We examined the effects of ATG on the early clinical outcomes of alloimmune events (development of de novo donor specific antibody and/or biopsy proven rejection) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…Previously, we have shown that ATG induction is associated with broad changes in the pediatric immune system regardless of nutritional status 24 . Some of these changes, including an increase in certain memory and/or senescent T‐cell types in both the CD4 and CD8 compartment, were observed to a greater extent in patients with obesity compared with those with normal nutrition and undernutrition.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Previously, we have shown that ATG induction is associated with broad changes in the pediatric immune system regardless of nutritional status 24 . Some of these changes, including an increase in certain memory and/or senescent T‐cell types in both the CD4 and CD8 compartment, were observed to a greater extent in patients with obesity compared with those with normal nutrition and undernutrition.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, we do not observe that children with malnu- Previously, we have shown that ATG induction is associated with broad changes in the pediatric immune system regardless of nutritional status. 24 Some of these changes, including an increase in certain memory and/or senescent T-cell types in both the CD4 and CD8 compartment, were observed to a greater extent in patients with obesity compared with those with normal nutrition and undernutrition. These findings point to the potential for an interaction between obesity and induction that may ) and no differences between nutritional status groups observed for CD8 Tem (p = .736).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 In paediatric KT patients, ATG induction is also associated with an increase in CD4 + effector memory and senescent CD57 + T cells that are associated with early event-free survival, suggesting its short-term clinical benefits. 55 In addition, it has been demonstrated that T-cell exhaustion correlates with improved outcomes in KT recipients. 56 Since ATG treatment causes increased accumulation of CD28 À CD8 + EMRA T cells (Figures 2c and d), we sought to scrutinise the effect of ATG on immunosenescent changes of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…CKD and related immunosuppressive therapies in paediatric patients accelerate immune senescence, including causing increases in CD57 + or CD28 − CD8 + T cells 54 . In paediatric KT patients, ATG induction is also associated with an increase in CD4 + effector memory and senescent CD57 + T cells that are associated with early event‐free survival, suggesting its short‐term clinical benefits 55 . In addition, it has been demonstrated that T‐cell exhaustion correlates with improved outcomes in KT recipients 56 .…”
Section: Discussionmentioning
confidence: 99%